2022
DOI: 10.3390/clockssleep4020022
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic Position and Excessive Daytime Sleepiness: A Systematic Review of Social Epidemiological Studies

Abstract: The objectives of this empirical study are to describe and discuss the current literature available on the relationship between excessive daytime sleepiness (EDS) and the socioeconomic position (SEP) as well as to provide recommendations for consideration of SEP in sleep medicine and biomedical research. Databases Medline/PubMed, Web of Science, Google scholar and Scopus were screened from January 1990 to December 2020 using PRISMA guidelines and 20 articles were included in the final synthesis. Nineteen studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 53 publications
0
6
0
1
Order By: Relevance
“…Like low SES, behavioral risk factors, such as smoking, alcohol and drug use, or eating disorders also negatively affect sleep quality. 23 In our study, SES could not be evaluated clearly because we could not reach a sufficient number of patients. However, further examination of sleep disorders, taking into account the impact of SES, will contribute to how social inequalities can cause sleep disorders and will guide prevention and treatment.…”
Section: Beck Depression Inventorymentioning
confidence: 89%
“…Like low SES, behavioral risk factors, such as smoking, alcohol and drug use, or eating disorders also negatively affect sleep quality. 23 In our study, SES could not be evaluated clearly because we could not reach a sufficient number of patients. However, further examination of sleep disorders, taking into account the impact of SES, will contribute to how social inequalities can cause sleep disorders and will guide prevention and treatment.…”
Section: Beck Depression Inventorymentioning
confidence: 89%
“…So, future studies in this region should consider moving forward the knowledge by using an objective measure of sleep to verify trends reported by local authors. There are also a lot of sleep disorders not studied, while a few such as OSA can be linked to other sleep disorders such as excessive daytime sleepiness [ 8 , 39 , 40 ], and thus have to be studied. Finally, the heterogeneity of SES involved a deep consideration of the sociological approaches and psychological theories in biomedical research, in order to be able to accurately capture this complex concept.…”
Section: Discussionmentioning
confidence: 99%
“…Health inequalities are associated with economic and societal impact on every government, regardless of GDP and the global well-being of an entire population [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 ]. Health inequalities can be observed with the cardiovascular system [ 9 ], respiratory system [ 10 ] or sleep mechanisms [ 1 , 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, several studies reported that sleep health and sleep disturbance are correlated to SES. Poor income, low education, unemployment, and difficult living conditions are reportedly associated with poor sleep quality, insomnia, and excessive daytime sleepiness [ 15 , 16 ]. Moreover, a meta-analysis showed that the influence of SES on sleep health can be measured objectively and quantitatively through actigraphy or polysomnography [ 17 ].…”
Section: Introductionmentioning
confidence: 99%